E-cigarette Use Among Middle and High School Students in New York City Before and After Passage of Tobacco 21 - Indira Debchoudhury MPH; Shannon M Farley DrPH; Kristi Roods MPH; Achala Talati DO, MPH; John Jasek MPA (SAGE Publishing, 2022)
Introduction Despite declines in cigarette smoking in the US, electronic cigarette (e-cigarette) use has increased among middle and high school students. In 2014, New York City (NYC) implemented Tobacco 21 (T21) to prohibit sales to anyone under age 21. Our study goal was to measure the effectiveness of T21 on e-cigarette use. Methods We used the New York State (NYS) Youth Tobacco Survey-a biennial, school-based, self-administered survey. We explored middle (N = 5249) and high (N = 7296) school NYC students' (male and female) current (past 30 days') e-cigarette use from 2014 (pre-T21) to 2018 (post-T21). Results were compared with students in the rest of NYS (ROS). Bivariate and multivariable logistic regression analyses assessed correlates of e-cigarette use, beliefs about harmfulness, addictiveness, and susceptibility. Results NYC high school students' current e-cigarette use increased from 2014 to 2018 (8.1% vs 23.5%, P < .001). Middle school students' use increased between 2014 (4.8%) and 2016 (9.0%) yet reversed by 2018 (5.7%) (2014 vs 2018, P = .576). ROS middle school (2.2% vs 7.4%, P < .001) and high school (12.0% vs 29.3%, ( P < .001) use increased from 2014 to 2018. Willingness to try e-cigarettes among those who had never tried an e-cigarette was twice as high (AOR = 2.19, 95% CI = 1.15-3.17) among NYC high school students in 2018 compared with 2014. Conclusions E-cigarette use increased among NYC high school students despite T21. T21 may have reduced use among middle school students over time. Programs that denormalize e-cigarettes and policies that further restrict access are needed to decrease youth e-cigarette use.